Cooling Intervention (MUSTCOOL) for Prevention of Lower Extremity Ulcer Recurrence: A Randomized Controlled Trial - Kelechi, Teresa J. (J Wound Ostomy Continence Nurs, 2021)
PURPOSE: The purpose of this study was to test our MUSTCOOL cooling patch intervention on the incidence of venous leg (VLU) and diabetic foot ulcer (DFU) recurrence over a previously healed wound. DESIGN: 6-month randomized controlled trial. SUBJECTS AND SETTING: The target population was individuals with previously healed ulcers receiving care in outpatient wound centers in the Southeastern region of the U.S. participated in the trial. The sample comprised 140 individuals with recently healed ulcers, their average age was 62.4 years (SD 12 yrs.); 86 (61.4%) were male; and 47 (33.6%) were Black or African American. METHODS: Participants were randomized to the MUSTCOOL or placebo patch. Both groups received instructions to apply the patch 3 times per week, and engage in standard of care including compression and leg elevation (VLU) or therapeutic footwear and hygiene (DFU). Demographic data were collected at baseline, and incidence measures taken at 1, 3, and 6 months. We also studied whether new ulcers developed on the adjacent leg or foot. Data were reported in frequencies/percentages. RESULTS: One hundred seventeen participants (84%) were analyzed who completed 6 months of study participation. Thirteen percent (9/69) and 17% (12/69) developed a recurrent or new VLU, respectively; 29% (14/48) and 13% (6/48) developed a recurrent or new DFU, respectively. One person in the DFU group developed both a recurrent and new ulcer. For 9 recurrent VLUs, 6 (66.7%) recurred in the MUSTCOOL group and 3 (33.3%) receiving the placebo. Of the 15 recurrent DFUs (includes individual that developed both a recurrent and new ulcer), 10 (66.7%) recurred in the MUSTCOOL group and 5 (33.3%) receiving the placebo. CONCLUSIONS: While the incidence of ulcer recurrent was slightly higher in the MUSTCOOL group, this finding was not considered clinically relevant. Overall ulcer recurrence during the 6-month study period was lower than reports in the literature, the time frame in which recurrence rates are highest. TRIAL REGISTRATION: The study was prospectively registered with ClinicalTrials.gov on December 10, 2015 (Identifier: NCT02626156) https://clinicaltrials.gov/ct2/show/NCT02626156.